Netflix Games, czyli strategie platformy Netflix wobec gier cyfrowych - Prałat, Marta; Szymańska, Anna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2026)
This paper analyses the strategy of streaming platforms in terms of interactive content–from interactive films to video games. The study covers the years 2017–2025 and focuses on the changing strategy of the Netflix platform regarding new forms of interactive entertainment over the years. The first part outlines a detailed history of this segment based on the most important media reports, which gives a coherent overview of the evolving strategy. The second part of the article presents findings from a detailed analysis of the video games library available to Polish subscribers. These results confirm the initial thesis: after the period of experimenting with interactive content in the years 2017-2024, since mid-2024, Netflix has shifted its focus to producing widely available content for the whole family.